Bacillus Licheniformis BS12 AS BIOFERTILIZER TO IMPROVE MAIZE GROWTH - Khazaal, Ali (Iraqi Journal of Science, 2024)
The Bacillus was isolated from Rhizosphere of different plants. All the isolates have the ability to produce Indole Acetic Acid (IAA)and the BS12 has the efficient strain in the IAA production with 8.4 μg/ml, this strain is able to produce Ammonia, solublize phosphate and fix the Nitrogen and it belongs to Bacillus licheniformis. The BS12 has able to improve the maize growth by enhance to germination percent, shoot high, root high, dry mass and nutrient concentration comparing to control.